Asymptotic behavior of solutions to a nonlinear Stefan problem with different moving parameters. (October 2016) - Zhao, Yonggang; Wang, Mingxin
Abstract: This paper deals with a nonlinear diffusion equation with double free boundaries possessing different moving parameters. We present the spreading–vanishing dichotomy and threshold between spreading and vanishing. Moreover, when spreading happens, using the zero number argument we provide sharp estimates of spreading speeds of expanding fronts, and describe how the solution approaches the semi-wave.